Prevalence of normal coronary angiography in the acute phase of suspected ST-elevation myocardial infarction: experience from the PRAGUE studies - Widimsky, P; Stellova, B; Groch, L; Aschermann, M; Branny, M; Zelizko, M; Stasek, J; Formanek, P; PRAGUE Study Group Investigators (The Canadian journal of cardiology, 2006)
BACKGROUND: Acute ST-elevation myocardial infarction in patients with normal coronary arteries has previously been described, but coronary angiography in these patients was performed after the acute phase of the infarction. It is possible that these patients did not have normal angiograms during the acute phase (transient coronary thrombosis or spasm were usually suspected to be the cause). Information on the prevalence of truly normal coronary angiograms during the acute phase of a suspected ST-elevation myocardial infarction is lacking. PATIENTS AND METHODS: The Primary Angioplasty in patients transferred from General community hospitals to specialized PTCA Units with or without Emergency thrombolysis-1 (PRAGUE-1) and PRAGUE-2 studies enrolled 1150 patients with ST-elevation acute myocardial infarction, in whom 625 coronary angiograms were performed within 2 h of the initial electrocardiogram. A simultaneous registry included an additional 379 coronary angiograms performed during the ST-elevation phase of a suspected myocardial infarction. Thus, a total of 1004 angiograms were retrospectively analyzed. A normal coronary angiogram was defined as one with the absence of any visible angiographic signs of atherosclerosis, thrombosis or spontaneous spasm. RESULTS: Normal coronary angiograms were obtained for 26 patients (2.6%). Among these, the diagnosis at discharge was a small myocardial infarction in seven patients (0.7%), acute (peri)myocarditis in five patients, dilated cardiomyopathy in four patients, hypertension with left ventricular hypertrophy in three patients, pulmonary embolism in two patients and misinterpretation of the electrocardiogram (ie, no cardiac disease) in five patients. Seven patients with small infarctions underwent angiography within 30 min to 90 min of complete relief of the signs of acute ischemia, and thus, angiograms during pain were not taken. None of the 898 patients catheterized during ongoing symptoms of ischemia had a normal coronary angiogram. Spontaneous coronary spasm as the only cause (without underlying coronary atherosclerosis) for the evolving infarction was not seen among these 898 patients. Thus, the causes of the seven small infarcts in patients with normal angiograms remain uncertain. CONCLUSIONS: The observed prevalence of normal coronary angiography in patients presenting with acute chest pain and ST elevations was 2.6%. Most of these cases were misdiagnoses, not infarctions. A normal angiogram during a biochemically confirmed infarction is extremely rare (0.7%) and was not seen during the ongoing symptoms of ischemia.
Keywords: senioři; Stroke Volume; elektrokardiografie; Prevalence; senioři nad 80 let; troponin; echokardiografie; Retrospective Studies; Creatine Kinase, MB Form; Česká republika; výsledek terapie; Echocardiography; Middle Aged; mužské pohlaví; infarkt myokardu; prevalence; funkce levé komory srdeční; Adult; Czech Republic; tepový objem; koronární angiografie; Myocardial Infarction; Coronary Angiography; Aged, 80 and over; převodní systém srdeční; Electrocardiography; kreatinkinasa, forma MB; ženské pohlaví; retrospektivní studie; Humans; Troponin; biologické markery; Heart Conduction System; Angioplasty, Balloon, Coronary; lidé středního věku; balónková koronární angioplastika; dospělí; Biomarkers; Female; Aged; Treatment Outcome; lidé; Male; Ventricular Function, Left